Studi Empiris Pada Perusahaan yang Mendapat Penilaian PROPER dari Kementerian Lingkungan Hidup dan Hutan dan Terdaftar Di Bursa Efek Indonesia Tahun 2017-2021 - Domineka, Billy Ghozali (Jurnal KIAFE, 2023)
This research aims to provide awareness for companies not only to generate maximum profits, but also how these profits can provide benefits to society, because company activities in generating profits will have consequences for the environment around them. The results of this research state that: (1) Environmental performance has a negative and significant effect on corporate financial performance. (2) Environmental costs cannot affect corporate financial performance. (3) Environmental performance cannot influence corporate social responsibility disclosure. (4) Environmental costs cannot influence corporate social responsibility disclosure. (5) Corporate social responsibility disclosure has a negative effect on corporate financial performance. (6) Environmental performance cannot indirectly influence corporate financial performance with corporate social responsibility disclosure as an intervening variable. (7) Environmental costs can indirectly influence corporate financial performance with corporate social responsibility disclosure as an intervening variable.